We have the given polynomial as P(x) = -x(- x - 2)2(x + 2)

P(x) = -x(- x - 2)2(x + 2)

=> P(x) = -2x(-x - 2)(x + 2)

=> P(x) = 2x(x + 2)(x + 2)

=> P(x) = 2x(x + 2)^2

The zeros are 0 and -2

**Therefore the required zeros are**

**-2 with multiplicity 2 and 0 with multiplicity 1.**

Given the polynomial P(x) = -x (-x-2)^2 (x+2)

We need to determine the zeros of P(x).

We notice that P(x) is already written in its factors form.

Then the zeros of P(x) are the zeros of the factors.

The zero of -x is 0

The zero of (-x-2)^2 is -2

The zero of (x+2) is -2.

Then the zeros of P(x) are 0 and -2.

Since the factor (-x-2)^2 is a square , then the multiplication is 2.

Then the zeros are :

**x1 = 0 ==> multiplication is 1**

**x2= -2 => multiplication is 2.**

## See eNotes Ad-Free

Start your **48-hour free trial** to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Already a member? Log in here.